Orphan response regulator NnaR is critical for nitrate and nitrite assimilation in Mycobacterium abscessus - Simcox, Breven S.; Rohde, Kyle H. (Frontiers in Cellular and Infection Microbiology, 2024)
Mycobacterium abscessus (Mab) is an opportunistic pathogen afflicting individuals with underlying lung disease such as Cystic Fibrosis (CF) or immunodeficiencies. Current treatment strategies for Mab infections are limited by its inherent antibiotic resistance and limited drug access to Mab in its in vivo niches resulting in poor cure rates of 30-50%. Mab’s ability to survive within macrophages, granulomas and the mucus laden airways of the CF lung requires adaptation via transcriptional remodeling to counteract stresses like hypoxia, increased levels of nitrate, nitrite, and reactive nitrogen intermediates. Mycobacterium tuberculosis (Mtb) is known to coordinate hypoxic adaptation via induction of respiratory nitrate assimilation through the nitrate reductase narGHJI. Mab, on the other hand, does not encode a respiratory nitrate reductase. In addition, our recent study of the transcriptional responses of Mab to hypoxia revealed marked down-regulation of a locus containing putative nitrate assimilation genes, including the orphan response regulator nnaR (nitrate/nitrite assimilation regulator). These putative nitrate assimilation genes, narK3 (nitrate/nitrite transporter), nirBD (nitrite reductase), nnaR, and sirB (ferrochelatase) are arranged contiguously while nasN (assimilatory nitrate reductase identified in this work) is encoded in a different locus. Absence of a respiratory nitrate reductase in Mab and down-regulation of nitrogen metabolism genes in hypoxia suggest interplay between hypoxia adaptation and nitrate assimilation are distinct from what was previously documented in Mtb. The mechanisms used by Mab to fine-tune the transcriptional regulation of nitrogen metabolism in the context of stresses e.g. hypoxia, particularly the role of NnaR, remain poorly understood. To evaluate the role of NnaR in nitrate metabolism we constructed a Mab nnaR knockout strain (MabΔnnaR) and complement (MabΔnnaR+C) to investigate transcriptional regulation and phenotypes. qRT-PCR revealed NnaR is necessary for regulating nitrate and nitrite reductases along with a putative nitrate transporter. Loss of NnaR compromised the ability of Mab to assimilate nitrate or nitrite as sole nitrogen sources highlighting its necessity. This work provides the first insights into the role of Mab NnaR setting a foundation for future work investigating NnaR’s contribution to pathogenesis.